The Consumption Patterns of Hassawi Rice and the Saudi Population Awareness of Its Nutritional Value - Ahlam Saleh Alhajri; Maha Loutfi Hadid (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study examines the consumption patterns of Hassawi rice among citizens of Saudi Arabia, emphasizing their awareness of its nutritional benefits. 67.4% of 1,017 respondents to a standardized questionnaire reported eating Hassawi rice. Younger and married participants consumed more (p = 0.008 and 0.000, respectively). 92.4% of Eastern respondents ate rice, compared to lower percentages in other regions (p = 0.000). Awareness of the nutritional benefits was notably elevated; 56% of participants recognized Hassawi rice as possessing greater nutritional value relative to other rice kinds (p = 0.000). Furthermore, health-related factors affected consumption, with individuals suffering from obesity or diabetes indicating reduced intake (p < 0.05). The favored culinary techniques encompassed classic meals like Kabsa and Madroba, primarily employing plant oils or butter for their preparation. Participants recognized the principal nutrients of Hassawi rice as antioxidants, carbs, and vitamins. Notwithstanding its popularity, obstacles to consumption encompassed perceptions of elevated pricing and lack of availability in specific places. This study emphasizes the need to promote Hassawi rice for Saudi dietary diversity and health, especially in low-consumption areas. Hassawi rice's cultural significance and possible benefits in normal diets are highlighted. More research is needed on the long-term health effects of Hassawi rice.